MENAFSIR ULANG BENTHAM DAN MALTHUS TENTANG KONSEP KONSUMSI BERKELANJUTAN - Jazila Zahroul Hasby; Septia Wulandari; Ahmad Syaifuddin Romli; Reza Hilmy Luayyin (Wasīlah: Journal Of Sharia Sciences, 2025)
Global economic developments have shifted consumption patterns toward short-term gratification, often neglecting environmental sustainability. This study aims to examine the relevance of classical economic thought—specifically that of Jeremy Bentham and Thomas Robert Malthus—regarding sustainable consumption from the perspective of university students. Using a qualitative library research approach, supported by questionnaires and limited interviews, the findings reveal that most students understand Bentham’s utilitarian principle of maximizing collective happiness and Malthus’ theory of limited natural resources. However, real-life application remains limited, with practical considerations such as affordability and convenience taking precedence. Students tend to adopt a hybrid perspective that combines ethical values with ecological awareness. This study highlights the importance of integrating classical theories with modern sustainability challenges to foster more conscious consumption behavior, as well as the strategic role of higher education in promoting behavioral change among the younger generation. Kata kunci: Konsumsi Berkelanjutan, Jeremy Bentham, Thomas Malthus, Mahasiswa, Utilitarianisme, Keterbatasan Sumber Daya